FAKTOR PENYEBAB PERNIKAHAN PADA USIA REMAJA DI WILAYAH KERJA PUSKESMAS JONGAYA MAKASSAR - Wirawati Amin; Hidayati, Hidayati; Afriani, Afriani (Journal of Innovation Research and Knowledge, 2024)
Currently, teenagers are faced with many challenges which of course come from themselves or from their parents and families. These challenges can make adolescents an opportunity for risky sexual behavior, including environmental influences with peers, early menarche, and the influence of various media. As a result of this, adolescents become vulnerable to sexually transmitted diseases, early marriage, and unwanted pregnancies. The purpose of this study was to analyze several factors that cause marriage at a young age in the working area of ​​the Jongaya Public Health Center Makassar. This research is a quantitative descriptive research, with a cross sectional design approach. The number of samples as many as 79 people using purposive sampling technique. Statistical data analysis technique using Chi Square Test. The results obtained are that there is a relationship between knowledge and parental income with the incidence of early marriage at the Jongaya Health Center Makassar City, there is no relationship between attitudes and parental roles on the incidence of early marriage at the Jongaya Health Center Makassar City. The conclusion of this study is that there is a relationship between knowledge and parental income with the incidence of early marriage at the Jongaya Health Center Makassar City; there is no relationship between attitudes and the role of parents on the incidence of early marriage at the Jongaya Health Center Makassar City. Suggestions that can be given are to increase health promotion by providing education to adolescents, especially about maturing the age of marriage